Effect of Pancreatic Fistula on Recurrence and Long-Term Prognosis of Periampullary Adenocarcinomas after Pancreaticoduodenectomy. Issue 12 (December 2016) - Serrano, Pablo E.; Kim, Dowan; Kim, Peter T.; Greig, Paul D.; Moulton, Carol-Anne; Gallinger, Steven; Wei, Alice C.; Cleary, Sean P.
Pancreatic fistula (PF) is common after pancreaticoduodenectomy (PD). Its effect on recurrence and survival is not known. Retrospective study of patients undergoing PD for periampullary adenocarcinomas (2000–2012). Standard statistical analyses were performed to determine the impact of PF on disease-free survival (DFS) and overall survival (OS). There were 634 PDs (pancreatic adenocarcinoma: 347, other periampullary adenocarcinomas: 287). Any-grade PF developed in 81/634 (13%). Perioperative mortality rate was 1.7 per cent (11/634), higher in patients with PF (10 vs 0.5%, P < 0.001). In multivariable analysis, PF significantly reduced DFS in pancreatic [hazard ratio (HR) = 1.6, 95% confidence-interval (CI): 1.1–2.6, P = 0.043] but not in other periampullary adenocarcinomas [HR = 1.3 (95% CI: 0.8–2.2), P = 0.45]. Positive lymph nodes, margins, and high-grade histology were associated with decreased DFS and OS. Adjuvant therapy was associated with improved OS in pancreatic [HR = 0.7 (95% CI: 0.5–0.9), P = 0.02] but not in other periampullary adenocarcinomas [HR = 1.14 (95% CI: 0.8–1.7), P = 0.49]. PF did not alter OS in either group. After PD, PF is associated with decreased DFS in pancreatic but not in other periampullary adenocarcinomas. This decrease DFS did not alter OS. Tumor grade, lymph nodes, and resection margin status are associated with DFS and OS.